The role of serum vitamin D in patients with normal ovarian reserve undergoing the first IVF/ICSI cycle - Luo, Rong; Wang, Jiahui; Yang, Yu; Xu, Cen; Yang, Minyan; Zhu, Dandan; Wang, Jia; Zhang, Ping; Ge, Hongshan (Frontiers in Endocrinology, 2023)
Background: The debate over the impact of vitamin D in assisted reproduction continues. The purpose of our study was to assess embryo quality and pregnancy outcomes among groups with different levels of vitamin D after the first in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycle in patients with normal ovarian reserve (NOR). Methods: Patients in this retrospective cohort study were divided into three groups: severe vitamin D deficiency group (25OH-D < 10 ng/ml), vitamin D deficiency group (10 ng/ml ≤ 25OH-D < 20 ng/ml), and non-vitamin D deficiency group (25OH-D ≥ 20 ng/ml). The primary outcome was clinical pregnancy, while the secondary outcomes were mature oocytes, oocyte fertilization, available cleavage embryos, available blastocysts, biochemical pregnancy, early abortion, and embryo implantation. A modified Poisson regression model and multiple linear regression analysis were conducted for the multivariate analysis. Results: 264 NOR patients undergoing the first IVF/ICSI cycles were included. For the primary outcome, there was no significant difference in clinical pregnancy between the severe vitamin D deficiency group and the other two groups (vitamin D deficiency group: adjusted RR = 1.026; 0.780 - 1.350; P = 0.854; non-vitamin D deficiency group: adjusted RR = 1.092; 0.743 - 1.605; P = 0.652). For all secondary outcomes, no significant differences were observed among the severe vitamin D deficiency, vitamin D deficiency, and non-vitamin D deficiency groups (P > 0.05). Exploratory subgroup analyses concerning the season of embryo transfer, phase of embryo transferred, and endometrial thickness, as well as the sensitivity analysis using logistic regression models for the primary outcome, revealed comparable clinical pregnancy rates among the groups (P > 0.05). Subgroup analysis concerning ovarian stimulation protocol indicated that in the subgroup of gonadotrophin-releasing hormone (GnRH) antagonist protocol, the clinical pregnancy rate of the non-vitamin D deficiency group was significantly higher than that of the other two groups (P < 0.05). Conclusion: Serum vitamin D level was not associated with embryo quality and pregnancy outcomes for patients with NOR. Further studies with greater sample sizes and a longer follow-up period are needed to elucidate the relationships between vitamin D levels and IVF outcomes.